2011
DOI: 10.5505/1304.7361.2011.89804
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Level of Burnout and Job Satisfaction in Emergency Department Personnel

Abstract: SUMMARY Objectives This study investigates to determine whether there is a relationship between perceptions of burnout and job satisfaction for working in emergency services. Methods This study is conducted through a survey on medical doctor and staff working in emergency services ÖZET AmaçBu araştırma, acil servis çalışanlarının tükenmişlik ile iş doyumu düzeyleri arasında ilişki olup olmadığını belirlemek amacıyla yapılmıştır. Gereç ve YöntemAraştırma, Kocaeli ilindeki 50 ve üzeri yatak kapasitesine sahip ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In this study, though a weak association between personal success and work satisfaction was noted, the results were consistent with the literature. The reason for the weak relationship between personal success and work satisfaction might be the high patient/nurse ratios in Turkey and high patient circulation (Akpınar & Tas , Demirgoz Bal ). However, this weak association between personal success and work satisfaction may occur since nurses may lack positive feedback in the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, though a weak association between personal success and work satisfaction was noted, the results were consistent with the literature. The reason for the weak relationship between personal success and work satisfaction might be the high patient/nurse ratios in Turkey and high patient circulation (Akpınar & Tas , Demirgoz Bal ). However, this weak association between personal success and work satisfaction may occur since nurses may lack positive feedback in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers indicated that nurses working in neonatal intensive care units (Aytekin & Kurt ) and emergency service (Kavlu & Pınar ) had medium level scores of internal, external and total job satisfaction. Akpınar and Tas () concluded that as the internal satisfaction levels of emergency service employees increases, emotional exhaustion and depersonalisation levels decrease, and positive, though weak, relationships between personal accomplishment and perceptions of internal satisfaction and general satisfaction were noted. Braithwaite () observed that among nurses with high burnout levels, job satisfaction decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Overcrowding is one of the most important problems in the ED which causes decrease in EM popularity. It causes not only motivation disorders of employee but also degradation of the quality of care, increased costs and patients' dissatisfaction [2] [3].…”
Section: Introductionmentioning
confidence: 99%